Successful treatment of fasciola hepatica with metronidazole in a child: A case report - KEPENEKLİ KADAYİFCİ, EDA; YAPICI, ÖZGE; BATU, UTKU; TUTAR, ENGİN (My University, 2022)
Fasciola hepatica is a zoonotic liver trematode that usually causes infection in cattle and sheep, and is transmitted to humans by consuming water and aquatic plants contaminated with metacercaria. The detection of Fasciola eggs in stools, serological evaluation and radiological evaluation are essential for diagnosis. Triclabendazole is the first-line therapy for fascioliasis. However, as triclabendazole is not an easily accessible drug in countries such as Turkey, it reveals a quest for alternative therapies. In this report, we present a 10-year-old boy with fascioliasis successfully treated with a course of metronidazole 1.5 g/ day for 3 weeks in 2020. During the follow-up, eosinophilia and radiological findings completely recovered. Here we report a case of pediatric fascioliasis that was cured with metronidazole successfully.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Fasciola hepatica; Fascioliasis; Metronidazole; Triclabendazole